Analisis Intensitas Penggunaan Gadget Dan Pendampingan Orang Tua Dalam Meningkatkan Daya Retensi Hafalan Surat (Studi Kasus Di Satuan Pendidikan Anak Usia Dini Guna Bakti Mandiri) - Isti Komariah (FKIP UNSULTRA, 2026)
This study aims to analyze the relationship between gadget use intensity, parental guidance, and memorization ability of short surahs in early childhood. The study used a descriptive qualitative approach and was conducted at the Guna Bakti Mandiri Early Childhood Education Center (PAUD) from March to April 2026. The subjects were 18 children aged 5–6, four teachers as supporting informants, and parents as additional informants. Data collection techniques included observation, semi-structured interviews, documentation, and open-ended questionnaires. Data analysis employed the Miles and Huberman interactive model through data reduction, data presentation, and conclusion drawing. The results showed that children's gadget use intensity was high, dominated by digital entertainment activities. Children with high levels of gadget use tended to have low memorization retention, characterized by difficulty focusing, being easily distracted, and frequently forgetting. Conversely, children with moderate levels of gadget use, accompanied by active parental guidance, demonstrated better and more stable memorization retention. Meanwhile, low levels of gadget use did not automatically result in high retention due to the lack of guidance and minimal repetition of memorization. These findings indicate that retention is influenced by the interaction between the intensity of gadget use, the quality of parental guidance, and other factors such as concentration, attention, and frequency of repetition. The implications of this study emphasize the importance of active parental guidance and educational management of gadget use. This research contributes to the understanding that gadget use can have a positive impact when managed appropriately to support early childhood learning.